Chapter Ripensare gli indicatori per le politiche per l'innovazione attraverso il Design-thinking - Lombardi, Mauro (Studi e saggi, 2021)
The final chapter contains the proposal to rethink the policies for innovation based on the approach defined Design thinking. Particularly important is the introduction of concepts such as global order parameters, referring to a systemic view of the techno-economic dynamics, and of a complementary methodology, called Agile. Based on the proposed framework, the decision-making space of different actors (private, public) in pursuing objectives at different levels is then analyzed. In this way a multi-level and multi-stakeholder decision making process can be enriched through a multiplicity of indicators in order to timely verify the efficiency of implementation process.